Dampak Dinamika Persaingan Harga Beli Sayur oleh Toke pada Kesejahteraan Petani di Pasar Koto Baru, Kec. X Koto, Kab. Tanah Datar - Nurfalah Nurfalah; Iiz Izmuddin (Lembaga Yasin AlSys, 2026)
Although the dynamics of price competition in the marketing of agricultural products have received attention in a number of studies, studies that specifically discuss the mechanism of competition in vegetable purchase prices by toke and its impact on farmers’ welfare in traditional markets remain limited. This study aims to analyze the dynamics of competition in vegetable purchase prices by toke and its impact on farmers’ welfare in Pasar Koto Baru, X Koto Subdistrict, Tanah Datar Regency. This study employed a qualitative approach with a case study design, involving participants consisting of farmers, toke, and representatives of the nagari government selected through purposive sampling. Data were collected through observation, interviews, and documentation, and were then analyzed using the stages of data reduction, data display, and conclusion drawing. The results showed that the determination of vegetable purchase prices had no official standard and was entirely determined by toke based on supply conditions and product quality. Competition among toke took place in a limited manner through verbal agreements, so prices tended to be uniform, whereas farmers were in the position of price takers with limited access to information and distribution. These conditions had an impact on income instability, imbalance in social relations, and psychological pressure on farmers. These findings contribute to the development of imperfect market theory while broadening understanding of traditional market dynamics from economic and social perspectives. This study concludes that price transparency and the strengthening of farmers’ bargaining positions are important aspects in improving farmers’ welfare. Therefore, the government and stakeholders need to expand access to information and improve the distribution system. The implications of this study include theoretical and practical contributions, while also opening opportunities for further research related to strengthening farmers’ institutions.